The charming quirks of others [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Isabel Dalhousie series., 2010)
Investigating allegations against a headmaster candidate for her alma mater, Isabel uncovers surprising truths that hit close to home and unwittingly upsets the father of her young son.